2023
DOI: 10.1038/s41598-022-26184-0
|View full text |Cite
|
Sign up to set email alerts
|

Air quality, meteorological variability and pediatric respiratory syncytial virus infections in Singapore

Abstract: Respiratory syncytial virus (RSV) is an important cause of respiratory illness among children. While studies have focused on the air-quality and climate dependence of RSV infections, few have been undertaken in South-East Asia where the burden of respiratory illness is among the highest across the globe. This study aimed to determine the relationships between climatic factors and air quality with RSV infections among children in Singapore. We obtained all laboratory-confirmed reports of RSV infections in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
(61 reference statements)
3
12
0
Order By: Relevance
“…Compared with central and southern regions, mean winter temperature in northern regions is lower [70]. Lower ambient temperature is a well-known positive predictor of RSV detection frequency [71][72][73]. Smaller studies tended to report a higher RSV prevalence, which is consistent with the small study effect.…”
Section: Discussionsupporting
confidence: 58%
“…Compared with central and southern regions, mean winter temperature in northern regions is lower [70]. Lower ambient temperature is a well-known positive predictor of RSV detection frequency [71][72][73]. Smaller studies tended to report a higher RSV prevalence, which is consistent with the small study effect.…”
Section: Discussionsupporting
confidence: 58%
“…45 Third, other studies have also reported an inverse relationship between levels of the same and other air pollutants and the rate of hospitalization for respiratory tract infections and RSV infection risk. [46][47][48] Interestingly, all these studies reporting these inverse relationships have been conducted in countries with tropical or subtropical climates, as is also the case in our country. This finding may suggest residual confounding by an unmeasured seasonal confounder or other bias present in countries with this climate.…”
Section: Discussionmentioning
confidence: 54%
“…Second, due to restrictions imposed during the COVID‐19 pandemic, levels of air pollutants decreased, but indoor stays also increased, which in some individuals may have increased exposure to indoor air pollutants and the risk of human‐to‐human transmission of RSV as a result of indoor crowding 45 . Third, other studies have also reported an inverse relationship between levels of the same and other air pollutants and the rate of hospitalization for respiratory tract infections and RSV infection risk 46–48 . Interestingly, all these studies reporting these inverse relationships have been conducted in countries with tropical or subtropical climates, as is also the case in our country.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has shown that meteorological conditions significantly affect air quality. In this paper, based on existing literature, temperature (C), wind speed (m/s) and rainfall (mm) were selected as meteorological indicators affecting air quality (Hoque et al, 2022;Asimakopoulos, 2012;Jacob et al, 2019;Querol, 2011;Zhang, 2020;Lee et al, 2023). In terms of socio-economic factors, according to the Environmental Kuznets Curve (EKC), there is an inverted "U"-shaped relationship between economic growth and environmental quality.…”
Section: Datamentioning
confidence: 99%
“…The influencing factors of air quality are divided into meteorological and social and economic factors. It has been shown that wind, relative humidity, and climate among meteorological factors have a significant impact on air quality (Hoque et al, 2022;Asimakopoulos, 2012;Jacob et al, 2019;Querol, 2011;Zhang, 2020;Lee et al, 2023). Researchers have confirmed the correlation between GDP and air pollution (Grossman and Krueger, 1991;Lee, 2009;Ngaravas et al, 2019;Plassmann, 2006;Ahmad et al, 2021).…”
Section: Introductionmentioning
confidence: 97%